2021
DOI: 10.3390/nu13082737
|View full text |Cite
|
Sign up to set email alerts
|

The Mean of Milk: A Review of Human Milk Oligosaccharide Concentrations throughout Lactation

Abstract: Human milk oligosaccharides (HMOs) are non-digestible and structurally diverse complex carbohydrates that are highly abundant in human milk. To date, more than 200 different HMO structures have been identified. Their concentrations in human milk vary according to various factors such as lactation period, mother’s genetic secretor status, and length of gestation (term or preterm). The objective of this review is to assess and rank HMO concentrations from healthy mothers throughout lactation at a global level. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 120 publications
10
126
1
1
Order By: Relevance
“…As reported in previous EFSA opinions (EFSA NDA Panel, 2019b, 2020a,b, 2021, human milk contains a family of structurally related oligosaccharides, known as HMOs, which is the third largest fraction of solid components. The highest concentrations of HMOs occur in human colostrum (20-25 g/L), and concentrations between 5 and 20 g/L occur in mature human milk (Thurl et al, 2010;Bode, 2012;Urashima et al, 2018).…”
Section: Intake Of 3'-sl From Human Milkmentioning
confidence: 90%
See 1 more Smart Citation
“…As reported in previous EFSA opinions (EFSA NDA Panel, 2019b, 2020a,b, 2021, human milk contains a family of structurally related oligosaccharides, known as HMOs, which is the third largest fraction of solid components. The highest concentrations of HMOs occur in human colostrum (20-25 g/L), and concentrations between 5 and 20 g/L occur in mature human milk (Thurl et al, 2010;Bode, 2012;Urashima et al, 2018).…”
Section: Intake Of 3'-sl From Human Milkmentioning
confidence: 90%
“…Table 4: Estimated daily intake levels of 3'-SL from average (800 mL) and high (1,200 mL) human milk intakes for infants of 6.7 kg bw, based on mean and high concentrations of 3'-SL of 0.19 g/L and 0.70 g/L, respectively, in mature human milk (Soyyılmaz et al, 2021) Daily intake levels (mg/kg bw) from 800 mL of human milk Daily intake levels (mg/kg bw) from 1,200 mL of human milk…”
Section: Target Populationmentioning
confidence: 99%
“…A review of HMO concentrations in mature human milk, pooled from 57 studies published between 1966 and 2020, identified the 15 oligosaccharides that were in greatest abundance [54]. All 15 HMOs were predicted within the model, and a biosynthetic network was constructed (Supplementary Figure S1), in which all of the enzymes except the cIGnT activity (10) were used.…”
Section: Network and Hmo Classificationmentioning
confidence: 99%
“…The most abundant HMOs include the 2′-fucosyllactose (2′-FL) which belongs to the fucosylated group. Lacto- N -tetraose (LNT) has been recently demonstrated to be the second most abundant HMO [ 27 ]. Others include the Lacto- N -neotetraose (LNnT), which belong to the neutral non-fucosylated [ 28 ].…”
Section: Human Milk Oligosaccharides: Structure and Compositionmentioning
confidence: 99%